Is Weekly Frequency of Yoga Practice Sufficient? Physiological Effects of Hatha Yoga Among Healthy Novice Women - Csala, Barbara; Szemerszky, Renáta; Körmendi, János; Köteles, Ferenc; Boros, Szilvia (Frontiers in Public Health, 2021)
Beneficial physical and physiological health outcomes of yoga practice are well-supported by empirical data. However, whether weekly frequency of training is sufficient to evoke positive changes, is still an open question. The present intervention study investigated the effects of 10 weekly sessions of beginner level hatha yoga with respect to indicators of physical fitness and physiological markers. 82 young women (mean age of 22.0 ± 3.83 years) participated in the study. The yoga group (N = 49) attended a yoga course consisting of 10 sessions (1.5 h each) on a weekly basis. The control group (N = 33) did not receive any intervention. BMI, body fat percentage, balance (one-leg-stand test with open and closed eyes, functional reach test), flexibility (side bend test, modified sit and reach test) core muscle strength (plank test) as well as resting heart rate (HR), and heart rate variability (HRV) were assessed 1 week before and after the course. Both frequentist and Bayesian analysis showed an improvement in flexibility and balance in the yoga group compared to the control group. The yoga group showed also increased core muscle strength. No changes with respect to BMI, body fat percentage, resting HR and HRV were found. Ninety minute beginner level hatha yoga classes were characterized by 93.39 HR and 195 kcal energy consumption on average. The present findings suggest that weekly setting of a 10-session long hatha yoga training leads to improvements in balance, flexibility and core muscle strength among healthy young women. However, for changes in BMI, body fat percentage, resting HR and HRV longer, and/or more intense interventions are needed.